Structural Optimization of the Brake Pedal using Artificial Intelligence - Akçay, Özlem; İlkılıç, Cumali (My University, 2023)
In this study, weight reduction was performed on the brake pedal, which is one of the most important parts of the braking system, by using topology and shape optimi-zation, one of the structural optimization methods, respectively. The aim of the study is to develop an optimal design that reduces vehicle weight by finding the optimal material distribution for the brake pedal. The weight reduction process was carried out in two steps. In the first step, static analyses were performed on the starting brake pedal model. Later, topology optimization was performed for weight reduction pur-poses. After the topology optimization, new brake pedal design was created and weight reduction was performed. In the second step, shape optimization was per-formed using a genetic algorithm to obtain the optimal dimensions of the brake pedal. According to the optimization results, the weight of the design was reduced from 437 grams (g) to 326 grams (g) by topology optimization in the first step. So the new de-sign is 25.4% lighter compared to the first design. Later, as a result of shape optimiza-tion performed using a genetic algorithm, the weight was reduced from 326 g to 298 g and the optimal dimensions of the brake pedal were determined. Thus, with shape op-timization, a lighter brake pedal design of about 8.5% was achieved compared to to-pology optimization. As a result, the weight has been reduced from 437 g to 298 g, and the weight of the ideal brake pedal model is 31.8% lighter compared to the main model.
Keywords: Structural analysis; Topology optimization; Genetic algorithm; Shape optimization; Brake pedal.